Trips flexibilities and access to essential medicines in South Africa - Duku, Elissa Amponsaa (Department of Commercial Law, 2022)
A number of opportunities are available to South Africa through the use of international intellectual property flexibilities that are targeted and designed to protect and preserve access to medicine and health care. This dissertation will discuss a number of reasons and influences that have an effect on South Africa's accessibility to medicine through the means of intellectual property. This dissertation first embarks on giving a synopsis of the affects patents have with regards to access to medicine. It further contends that the use of the TRIPS flexibility known as compulsory licence should be utilised to realise the need of access to medicines in South Africa, together with how the pricing system has a weighty effect with regards to access to medicines. The TRIPS flexibility has given WTO members the liberty to determine and customise their policy space with regards to TRIPS obligations in a manner that is interpreted and implemented that meets and reflects its citizen's needs. This dissertation seeks to find if South Africa has made use of such means of reflection in its policy space and its proactive prioritisation of access to medicines in South Africa.